2019
DOI: 10.1002/jpen.1530
|View full text |Cite
|
Sign up to set email alerts
|

Tolerability and Effects of the Use of Energy‐Enriched Infant Formula After Congenital Heart Surgery: A Randomized Controlled Trial

Abstract: Background Undernutrition is a common problem among children with congenital heart disease (CHD) and may lead to poorer surgical outcomes. A higher intake of energy during the postoperative period of CHD surgery seems to be associated with better outcomes. This study aimed to investigate the effect of the use of energy‐enriched formula (EE‐formula) compared with normocaloric formula during 30 days after CHD surgery. Methods A randomized controlled trial with patients undergoing heart surgery in a tertiary hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 14 publications
2
17
0
1
Order By: Relevance
“…Our study did not find a statistical difference in the incidence of diarrhea and fecal occult blood between the two groups, suggesting that critical postoperative infants with CHD can tolerate high-energy nutrition. Two other studies with similar results to the present study have also confirmed that high-energy formula does not increase gastrointestinal adverse effects such as vomiting and diarrhea in patients, nor cardiac, renal and hepatic adverse effects ( 20 , 21 ). Even if the patients in the study by Zhang et al ( 13 ) experienced a small amount of abdominal distention and gastric retention, they could be relieved by gastroprokinetic drugs without affecting the feeding process.…”
Section: Discussionsupporting
confidence: 90%
“…Our study did not find a statistical difference in the incidence of diarrhea and fecal occult blood between the two groups, suggesting that critical postoperative infants with CHD can tolerate high-energy nutrition. Two other studies with similar results to the present study have also confirmed that high-energy formula does not increase gastrointestinal adverse effects such as vomiting and diarrhea in patients, nor cardiac, renal and hepatic adverse effects ( 20 , 21 ). Even if the patients in the study by Zhang et al ( 13 ) experienced a small amount of abdominal distention and gastric retention, they could be relieved by gastroprokinetic drugs without affecting the feeding process.…”
Section: Discussionsupporting
confidence: 90%
“…Favorable effects were also shown by reduced use of diuretics and oxygen supplementation. 35 Favorable outcomes were also reported by Eveleens et al 34 , who found that critically-ill infants experience weight-for-age (WFA) Z-score following administration of nutrientdense food. These patients achieved the energy target which was determined to be two-fold of the resting energy expenditure.…”
Section: Role Of Nutrient-dense Formula For Infants With Disease-rela...mentioning
confidence: 65%
“…Also, the patients had increased serum albumin levels which indicated improvement of nutrition status. 31 Another study by Scheefer et al 35 linked the use of nutrient-dense formula with decreased LOS and use of antibiotics during 30 days after CHD surgery. Favorable effects were also shown by reduced use of diuretics and oxygen supplementation.…”
Section: Role Of Nutrient-dense Formula For Infants With Disease-rela...mentioning
confidence: 99%
See 1 more Smart Citation
“…Preoperative use of high energy formula has been associated with weight gain and decreased hospital stay and postoperative complications (50). Postoperative use of energy-and nutrient-dense formula has been found to improve weight gain in infants with CHD (1) and to decrease hospital stay and reduce antibiotic use in these patients (52). In line with these ndings, we observed a clinically and statistically signi cant weight gain (indicated by an increase in WFA z-score) when energy-and nutrient-dense formula was given preoperatively to malnourished infants with CHD.…”
Section: Resultsmentioning
confidence: 99%